2012
DOI: 10.1299/jtst.7.104
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis in Mixed Convection MHD flow of Nanofluid over a Non-linear Stretching Sheet

Abstract: This article deals with a numerical study of entropy analysis in mixed convection MHD flow of nanofluid over a non-linear stretching sheet taking into account the effects of viscous dissipation and variable magnetic field. The nanofluid is made of such nano particles as SiO 2 with pure water as a base fluid. To analyze the problem, at first the boundary layer equations are transformed into non-linear ordinary equations using a similarity transformation. The resultant equations are then solved numerically using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…They observed that the Lorentz force generates vortices near the magnetic sources and the number and strength of vortices depend strongly on Hartmann number. Martin et al [23] analyzed the impact of frictional heating on entropy generation in a MHD mixed convection flow of a nanofluid over a non-linear stretching sheet. They observed http://www.ispacs.com/journals/cna/2017/cna-00319/ International Scientific Publications and Consulting Services that the surface serves as a strong source of irreversibility due to higher entropy generation number near the surface.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the Lorentz force generates vortices near the magnetic sources and the number and strength of vortices depend strongly on Hartmann number. Martin et al [23] analyzed the impact of frictional heating on entropy generation in a MHD mixed convection flow of a nanofluid over a non-linear stretching sheet. They observed http://www.ispacs.com/journals/cna/2017/cna-00319/ International Scientific Publications and Consulting Services that the surface serves as a strong source of irreversibility due to higher entropy generation number near the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thermosolutal convection in Walters' (Model B') elastico-viscous rotating fluid permeated with suspended particles and variable gravity field in porous medium in hydromagnetics was investigated by Rana [10]. Matin et al [11] presented the MHD mixed convective flow of a nanofluid over a stretching sheet. Chand and and Rana [12] examined the oscillating convection of nanofluid in porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…exchangers. Matin et al [44] accomplished a numerical research on MHD mixed convection flow using SiO2-water nanofluids over a non-linear stretching sheet. Selimefendigil et al [45] carried out an investigation on entropy generation of nanofluids natural convection in entrapped trapezoidal cavities taking the influence of magnetic field into consideration.…”
Section: Physical Model and Numerical Methodsmentioning
confidence: 99%